Inventory of the land resources of the Serayu River Basin from a geomorphological viewpoint - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1984)
Indonesia is a developing country in which the potential land resources are not yet precisely known. To make use of the land resources in a rational and continuing way, regional development planning is needed. This planning can be done when an inventory and evaluation of the area concerned has been made, hence the inventory and evaluation of land resources forms an important prerequisite for planning the management, and utilization of the regions. The main aims of the research using the Serayu River Basin as a case study are: (1) to develop a method of land resources inventory at the first stage, i.e. the reconnaissance level, from a geomorphological viewpoint